Static and dynamics of a pump impeller with a balancing device. - Martsynkowskyy, Volodymyr A.; Zhulyov, Aleksey; Kundera, Czesław (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents the theoretical study of the system comprising an impeller and a balancing device. It deals with the dynamic analysis of the system, i.e., the axial vibrations of the impeller, and the system stability. The dynamic analysis took into account linearized hydrodynamic forces and moments generated in the longitudinal clearances of the seals of the impeller. The theoretical analysis was supplemented with a numerical example with characteristics determined for a real single-stage centrifugal pump.
Keywords: dynamic analysis; pump impeller; balance device; stability conditions